Antenatal dietary concordance among mothers and fathers and gestational weight gain: a longitudinal study - Figueroa, Roger (BMC Public Health, 2020)
BACKGROUND: Parent-child dietary concordance is associated with child diet, but the clinical implications of mother-father dietary concordance during pregnancy are unknown. This study evaluates antenatal mother-father dietary concordance and associations with gestational weight gain (GWG). METHODS: Mother-father (n = 111) dyads with low income reported their fruit/vegetable (FV), fast food (FF), and sugar-sweetened beverage (SSB) consumption frequency during the first trimester of pregnancy. From electronic health records, we collected height and self-reported pre-pregnancy weight and calculated pre-pregnancy body mass index (BMI). The primary outcome was excessive GWG for pre-pregnancy BMI. Dyads were categorized as healthy or unhealthy concordant (consuming similarly high or low amounts of FV, FF, or SSB), or mother-healthy or father-healthy discordant (consuming different amounts of FV, FF, or SSB). Multivariable and logistic regressions analyzed associations between dietary concordance and GWG. RESULTS: Mothers were Hispanic (25%), 43% White, 6% Black, and 23% Asian or Other. Most mothers were employed (62%) making <$50,000/year (64%). Average maternal GWG was 11.6 kg (SD = 6.40), and 36% had excessive GWG. Mothers in the mother-healthy discordant FV group (OR = 4.84; 95% CI = 1.29, 18.22) and the unhealthy concordant FF group (OR = 7.08; 95% CI = 2.08, 24.12) had higher odds for excessive GWG, compared to healthy concordant dyads. SSB concordance was associated with higher GWG in unadjusted, but not adjusted models. CONCLUSIONS: Mothers had higher risk for excessive GWG when both partners had unhealthy FF consumption frequency, and when fathers had unhealthy FV consumption frequency. These findings imply that fathers should be involved in educational opportunities regarding dietary intake during pregnancy.